Analisis Faktor-Faktor yang Mempengaruhi Tingkat Gaji di ELRUMI BATIK PEKALONGAN - Zidan Kafabih (Sahmiyya, 2023)
ELRUMI BATIK PEKALONGAN is a company engaged in the clothing sector. The level of salary paid to company employees is influenced by several factors such as years of service, level of education, job position. This study aims to analyze the factors that influence the level of salary and wages in BATIK ELRUMI PEKALONGAN. The research method used is a case study with data collection through observational interviews and documentation studies. The results of the study show that the factor of length of service is the factor that most influences the level of salary and wages in the company. Employees who have worked for a longer period tend to get higher salaries and wages than employees who have just worked at the company, there are four factors that affect employee salaries, such as the distance traveled by the company to the employee's place of residence (domicile), length of service, type of work. The conclusion from this analysis is that the length of service is the main factor that affects the level of salary in BATIK ELRUMI PEKALONGAN. This research can be a "window" for prospective employees who want to register with Elrumi Batik Pekalongan, that loyalty, which is directly proportional to length of service, is an important factor in determining company payroll